A Teologia da libertação e o pontificado do Papa Francisco à luz da interpelação dos pobres ao fazer teológico em Am 6, 1-7. - Pereira, Antonio Wauleson (2022)
The contemporary theological reflection has the arduous task of making the Revelation of God in the Sacred Scriptures speak to current reality with such force and relevance that it can promote an eminently evangelical praxis founded on the principles of the reign of God. The prophecy of the Amos‘ book shows that the poor people constitute an interpellation to theology and require from it the ability to scrutinize and transform the reality of suffering faced by the great-impoverished mass of our planet. Therefore, the objective of this research is to demonstrate how Latin American Liberation Theology and the pontificate of Pope Francis take seriously the interpellation of the poor people to theology according to the prophecy of Amos, more specifically the pericope of Am 6,1-7. Our hypothesis is that Latin American Liberation Theology and the pontificate of Francis move the theological activity and pastoral action of the current Church to heed the interpellation of the poor people present in the prophecy of Amos and in the reality of our days, that is, they promote a Church that listens and defends the marginalized population. By nature, this is bibliographic research, with a qualitative approach and a hermeneutic focus, having as theoretical basis, mainly, Sicre (1991; 2011; 2016), Schökel (1991), Aquino Júnior (2012; 2018), Gutiérrez (1985; 2000; 2014), Sobrino (1994; 2019) and the magisterium of Pope Francis (2013; 2018; 2019). The results show that any theological reflection or pastoral practice can ignore that one of the primordial missions of Christianity is to promote a freeing praxis in order to give dignity to the historical victims of the globalized misery that plagues our reality, the path for what constitutes the being and the act of a loyal Church to the proclamation of the reign of God carried out by Jesus. When developing the work, the relevance of the TdL and the pontificate of Francis was verified as ways of doing theology that consider the poor as their starting point, therefore, attentive to the prayer of the impoverished.